A meta-analysis of leadership and intrinsic motivation: Examining relative importance and moderators - Xue, Hanbing; Luo, Yifei; Luan, Yuxiang; Wang, Nan (Frontiers in Psychology, 2022)
This paper provides the first meta-analytic examination of the relationship between leadership and followers’ intrinsic motivation. In particular, we examined 6 leadership variables (transformational, ethical, leader-member exchange, servant, empowering, and abusive supervision) using data from 50 independent samples and 21,873 participants. We found that transformational leadership, ethical leadership, leader-member exchange (LMX), servant leadership, and empowering leadership were positively related to intrinsic motivation, whereas abusive supervision was negatively linked to intrinsic motivation. Although these leadership styles were associated with intrinsic motivation, they varied considerably in their relative importance. Empowering, ethical, and servant leadership emerged as the more important contributors to intrinsic motivation than transformational leadership. LMX showed a similar contribution with transformational leadership to intrinsic motivation. Effectiveness of leadership styles in relation to intrinsic motivation varied by power distance, publication year, and journal quality. Drawing on our findings, we discuss the theoretical and practice implications.